Immunnohistochemical determination of calbindin distribution in gastrointestinal tract organs and pancreas, and in hypophysis, adrenal medulla and kidneys of guinea pigs - Berrin Gençer Tarakçı; Sema Timurkaan (Eurasian Journal of Veterinary Sciences)
The distribution ol calbindin in thyroid, parathyroid, piluilary and adrenals, and in gastrointestinal tract epilhelium, pancreas and in Ihe kidney has been investigated immunohistochemically using an antiserum raised against the 28k Da calbindin from chicken duadenum. Epithelial cels of paralhyroid, adren, ileum and calan tailed to react with the antibodies, atthouqh immunoreactıvıty was found in kidney tubules, panereane endocrine cells, thyroid, pituitary and in the epithelial cells of slomach and duodenal mucosa. This Jocalizalian is suggested to be in a role for calbindin in the mechanisms of caıcrum mediated enoocnne cell situmulalion or of intracellular and extracellular calcium homeostasis.